Problematika Intervensi Sosial dalam Penanganan Covid-19 di Desa Mon Ara Bireuen-Aceh Menuju Normalisasi Massa - Zulham Zulham; Martunis Martunis (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The government through the Ministry of Health has been continuously outreaching and educating the public to understand health protocols, but the phenomena that occurred in Mon Ara Village, Makmur District, Bireuen Regency include; there are still many people who are lazy to wear masks, wash their hands with soap, and keep their distance, there are still many people who think that Covid-19 is just the engineering of certain elements, there are still people who think that Covid-19 is exaggerated, and there are still people who have the view that handling Covid-19 is the government's job. This study aims to determine community intervention on the governance of handling Covid-19 in Desa Mon Ara, Makmur District, Bireuen Regency. The theory used in this research is intervention theory. The research approach used is qualitative by using interview instruments, documentation and observation. The data obtained were analyzed descriptively. The results of the study explained that community intervention in the governance of handling Covid-19 in Desa Mon Ara, Makmur District, Bireuen Regency, mobilized the masses to be vaccinated. However, some people do not follow the regulations, so that the community's willingness to use masks is not optimal. Community intervention in the distribution of direct cash assistance (BLT) is another problem during Covid.